Acoustic investigations of the exterior and interior wall of a log house - Butkus, Donatas; Januševičius, Tomas (Journal of Environmental Engineering and Landscape Management, 2011)
With the rapidly changing environment and growing cities and increasing traffic flows the problem of noise pollution is becoming more and more relevant. As street networks continue developing and land prices are rising, houses are more and more often built close to especially noisy suburban streets. Traffic-generated noise accounts for up to 80% of the prevailing noise level. Many people build private houses from eco-friendly building materials, such as wood. The construction volumes of log houses, roadhouses and guest houses have increased. This article presents acoustic investigations of a log house's D nT,w measured under natural conditions in the natural environment – a constructed log house – and in a noise suppression chamber, analysing an element of the log wall. The log wall concerned was covered with log house heat-insulation materials and the obtained D nT,w results reached up to 58 dB.Article in English.Rąstinio namo išorinės ir vidinės sienos akustiniai tyrimaiSantrauka. Aplinkai kintant, didėjant miestams ir plečiantis transporto srautams, vis aktualesnė tampa triukšmo namuose problema. Plečiantis gatvių tinklams, brangstant žemei, vis dažniau namai statomi netoli užmiesčio gatvių, kuriose aukštas triukšmo lygis. Iki 80% vyraujančio triukšmo lygio – tai transporto keliamas triukšmas. Daugelis gyventojų statosi individualius namus, o jiems statyti renkasi ekologiškas medžiagas, pavyzdžiui, medieną. Vis daugiau statoma rąstinių namų, pakelės užeigų ar svečių namų. Aprašomi akustiniai rąstinio namo sienos tyrimai, atliki natūroje ir triukšmo slopinimo kameroje. Rąstinė siena dengiama populiariomis rąstinių namų šiltinimo medžiagomis. Tiriamas vidinės sienos triukšmo izoliavimo koeficientas.Reikšminiai žodžiai: medžiagų akustiniai tyrimai, rąstiniai namai, triukšmo slopinimo kamera.Акустические исследования наружной и внутренней стены бревенчатого домаРезюме. В связи с изменением окружающей среды, ростом городов и увеличением транспортных потоков возрастает актуальность проблемы бытового шума. По мере развития уличной сети, роста стоимости земли строительство домов все чаще ведется на загородных улицах, отличающихся высоким уровнем шума. Шум, вызываемый транспортом, составляет до 80 % преобладающего шума. Многие жители строят индивидуальные дома и выбирают для их строительства экологичные материалы, такие, как древесина. Увеличивается строительство бревенчатых домов, придорожных кафе или гостевых домов. В статье описываются акустические исследования стены бревенчатого дома. Исследования проведены в естественных условиях и в шумоподавляющей камере. Бревенчатая стена покрывается популярными материалами, используемыми для утепления бревенчатых домов. Исследуется условный фасад дома и коэффициент шумовой изоляции внутренней стены.Ключевые слова: акустические исследования материалов, бревенчатые дома, шумоподавляющая камера.